The effect of low-pressure plasma treatment on sunflower seed germination and sprouts growth rate - R. Lonlua (2020)
© Published under licence by IOP Publishing Ltd. This study presents the influence of low-pressure plasma treatment on germination behaviour of sunflower seeds (Helianthus annuus). Both peeled and unpeeled seeds were treated with Ar plasma. The plasma was characterized using OES for understanding of physical and chemical species in the plasma. The physical properties and chemical properties of the samples were studied using SEM and water contact angle. Growth parameters including water uptake, seed germination, sprouts length and dry weight were also investigated. It was found that the surface roughness increased with the plasma-generating power. The water absorption decreased when the power increased and super hydrophilicity was achieved at a 100 W. The water uptake rate showed highest at 150 W plasma power. The highest rate of seed germination was found when the sunflower seeds were treated with plasma power of 150 W at 5-day sowing. Sprout length and dry weight increased with the plasma power as well. In summary, sunflower seeds treated by Ar plasma could improve seed germination rate, leading to significant change in wettability and growth parameter.